Applicability of the Moyers method for the estimation of the mesiodistal diameter of canines and premolars in patients of 12-18 years old (International Journal of Medical and Surgical Sciences, 2021)
One of the most universal methods used to predict the mesiodistal width of non-erupted canines and premolars is the one designed by Dr. Edison Moyers, an American orthodontist who, taking the Anglo-Saxon population as a reference, created percentile tables to estimate these values ​​in the maxilla and mandible. During the last decade, several researchers have discovered that, when applied to various populations, there are significant differences between predictions and actual values. In Cuba, it is widely used at a 50% probability for prediction in both sexes, but there are few reports of studies that validate its reliability and those that do exist use small samples of patients. For this reason, the objective of this research is to determine the applicability of the Moyers method at 50% probabilities for estimating the mesiodistal diameter of canines and premolars in patients 12-18 years of age. A descriptive and cross-sectional study was developed from July 2019 to February 2020 with a population of 125 patients, 62 females and 63 males, between 12 and 18 years old from Cuba. Measurements were made of the mesiodistal widths of the lower incisors, all the canines and premolars. Frequency distributions were made to the variables studied and the results were presented in statistical tables. To verify the existence of significant differences, the statistical t-Student test was used. The main results obtained were that the Moyers method tends to underestimate the values ​​for the female sex between 0.4-0.5 mm, and for the male sex between 0.6 and 0.7 mm, this difference being significant for men. It is concluded that the Moyers method cannot be applied in the population studied for the prediction of the mesiodistal width of canines and premolars
Keywords: Orthodontic; odontometry; unerupted tooth